Depicting abortion access on American television, 2005–2015. (February 2017) - Sisson, Gretchen; Kimport, Katrina
Despite an increasing number of restrictions on accessing abortion care in the United States, most Americans remain unaware of challenges to obtaining abortion. Theorists of abortion stigma have posited that entertainment media contribute to ongoing lack of knowledge about abortion care. Analyzing all plotlines that aired on American television between 2005 and 2015 in which abortion is considered (n = 89), we examine how access to abortion is portrayed, whether characters are able to surmount barriers, and what documented real-life challenges to access are missing from onscreen representations. We find that 42% show at least one barrier to accessing abortion care, most frequently illegality, cost of the procedure, and social stigma. Almost no barriers—including illegality—are insurmountable, and most are easily overcome for the characters seeking abortion. Some barriers, however, change how abortion is understood by a character such that she opts to continue the pregnancy. This underrepresentation of the difficulty of obtaining abortion care may contribute to public beliefs that abortion restrictions do not pose real challenges for women's access to abortion.